The weightings of Sheikh Muhammad bin Ali Al-Ethiopian - may God have mercy on him - (d. 1442 AH) On jurisprudential issues (in the chapter on the characteristic of prayer) (A comparative study) - Azza Ismail Abdel-Ghani Ali (Researchparks Publishing, 2023)
Sheikh Faqih, Al-Aswili, Al-Nahwi, Mohammed Ben Ali Al-Ethiopia, is one of the leading scholars who cared for the service of the Prophet Sunna, and forensically studied, taught and taught; He is one of the modern scholars who provided the Islamic Library with a lot of literature and prolific explanations in various Shari 'a sciences. God won him about Islam and Muslims. Based on the Ethiopian sheikh's scientific status, and the many writings in jurisprudence